Законодавче регулювання діяльності органів муніципального управління в кримських містах - Анісімова, О.С. (Культура народов Причерноморья, 2013)
В статье рассматриваются основные положения «Грамоты на права и выгоды городам
Российской империи» и особенности их внедрения в крымских городах. Введены в научный оборот
архивные сведения, проливающие свет на особенности создания муниципалитетов в Крыму.
Проанализированы статьи доходов и расходов городских самоуправлений, особенности самоуправления
в городах Крыма, показана их подконтрольность центральным органам власти.
Ключевые слова: муниципальное управление, городовая Дума, самоуправление, «Грамота на права и
выгоды городам Российской империи». У статті розглядаються основні положення «Грамоти на права і вигоди містам Російської
імперії» та особливості їх впровадження в кримських містах. Введено в науковий обіг архівні відомості,
що проливають світло на особливості створення муніципалітетів в Криму. Проаналізовано статті
доходів і витрат міст, особливості самоврядування в містах Криму, показана їх підконтрольність
центральним органам влади.
Ключові слова: муніципальне управління, міська Дума, самоврядування, «Грамота на права і вигоди
містам Російської імперії». The paper examines the main provisions of the "charter for the rights and benefits of the Russian
Empire" and especially their introduction in the Crimean cities. Introduced into science archival information
that shed light on the creation of municipalities in the Crimea. Analyzed the income and expenditure of urban
local governments, particularly governments in the cities of the Crimea area, their accountability to central
authorities.The article examines the legal basis of the activities of the municipal government in the cities of the
Crimea as an important factor in the development of the region. The author reveals the important role of
policeman reforms carried out on a "charter for the rights and benefits of the Russian Empire" and a number of
other laws that establish a system of municipal governance.Relevance of the problem raised is that the issues
related to the history of the formation and development of the municipalities in the cities of the Crimea today are
open. Since no studies in any way shed light on important aspects of the legal support of the municipalities. The
author made an analysis of the legislative acts of the central government, and involve a number of documents
issued by municipalities and city community.The article describes the main points of the establishment and
functional types of municipalities. Also, are the basic principles of self-government. The study found a number of
specific features that characterized the formation of city departments in the Crimea. These features again
emphasize the uniqueness of the Crimean region and its special place in the structure of the Russian Empire.
Keywords: munitsipalnnoe management, the policeman Duma, the government, "The Charter on the rights and
benefits of the Russian Empire."